PENCEGAHAN BULLYING DAN DISKRIMINASI MELALUI PELATIHAN TEKNIK BELADIRI PRAKTIS - Nova Liana; Aridhotul Haqiyah (An-Nizam, 2022)
The COVID-19 pandemic has hampered community activities in various fields, such as the economy, finance, education and health sectors. Based on the results of observations that have been made, there is still a lack of community knowledge about how to protect themselves from crimes and violence experienced, both on the road and at home. In addition, at this time there are also more and more crimes and violence against children, one of which is bullying and discrimination. This paper intends to increase knowledge, awareness, and public awareness of acts of bullying and discrimination carried out in RW 007, Kelapa Dua Wetan Village, Ciracas District, East Jakarta. The program of activities held was, "Socialization on Prevention of Bullying and Discrimination Through Practical Martial Techniques Training" for free. The purpose of this activity is to increase awareness, care and quick response to overcome and protect oneself from various crimes and violence. The method used is a combination of community outreach methods and training methods. Among its activities are conducting webinars, surveys, distributing posters/invitations to stop bullying and discrimination, as well as offline martial arts training. This implementation has a positive impact on the community, such as increasing knowledge and insight about the importance of preventing acts of bullying and discrimination, increasing interest and expertise in the field of martial arts, and how to protect oneself from various crimes.